Eating and Physical Activity Patterns in Day and Night Shift EMS Clinicians. (27th October 2021) - Mansouri, Tegan; Hostler, David; Temple, Jennifer L.; Clemency, Brian M.
Abstract: Objective: EMS clinicians work in shifts to provide 24-hour care. Shift work is linked with metabolic disease and over 70% of EMS clinicians report having overweight or obesity. Inability to store food in their vehicles combined with limited overnight dining establishments, and unpredictable job demands leads to reliance on convenience and fast foods. The objective of this study was to describe the eating and physical activity patterns among EMS clinicians on days on and off shift. Methods: EMS clinicians throughout the United States participated in a study involving four 24-hour monitoring periods. Participants wore activity monitors to measure physical activity level and remote food photography was used to collect dietary data on two work days and two days off. Repeated measures analysis of variance was conducted to compare energy and macronutrient intake and activity levels in day and night workers on and off shift. Results: We analyzed data from 39 EMS clinicians (29.7 + 8.5yrs old). Controlling for sex, those working night shifts consumed more kilocalories (p=.037) and total fat (p=.043) compared to day shift workers. Night shift workers had fewer steps (p = 0.045), more sedentary time (p = 0.053), and less moderate activity (p = 0.037) during a shift compared to day workers. Conclusion: Among EMS clinicians, night shift is associated with greater energy intake, and decreased physical activity during shifts. This may contribute to positive energy balance and weight gain overtime, increasing risk for metabolic disease.